2009
DOI: 10.1111/j.1745-4573.2009.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

ULTIMATE pH EXPLAINS VARIATION IN PORK QUALITY TRAITS

Abstract: The objective of this study was to determine the relationship between pH and fresh pork quality. Pigs (n = 988) PRACTICAL APPLICATIONSUltimate pH is becoming more widely used in industry applications to segregate carcasses prior to fabrication. The pH has been linked to several important attributes of pork quality, including water-holding capacity, tenderness and color. While it has been suggested that the pH measured at earlier time points postmortem can be used to predict pork quality, the results of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 19 publications
(29 reference statements)
5
37
1
Order By: Relevance
“…In contrast to this, Choi et al (2012) found differing cooking losses in LMs with comparable pH 45 min p.m., whereas Werner et al (2010a) found comparable grill losses in muscles with varying pH 45 min p.m. Band et al (2005) or Boler et al (2010) presented opposite results with higher cooking loss values in low pH 45 min p.m. pork. Cooking loss as well as drip loss are parameters to characterise the WHC of the tissue.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast to this, Choi et al (2012) found differing cooking losses in LMs with comparable pH 45 min p.m., whereas Werner et al (2010a) found comparable grill losses in muscles with varying pH 45 min p.m. Band et al (2005) or Boler et al (2010) presented opposite results with higher cooking loss values in low pH 45 min p.m. pork. Cooking loss as well as drip loss are parameters to characterise the WHC of the tissue.…”
Section: Resultsmentioning
confidence: 68%
“…This assumption is supported by Huff-Lonergan et al (2002), Boler et al (2010) or Omana et al (2014), who presented a positive relation between cooking loss and sensorially tougher meat, respectively, pork with higher shear force values. With regard to muscle structure parameters, the rate of pH decline only influenced the percentages of muscle fibres but not the CSA results.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Post-mortem pH is a large determinant of overall pork quality impacting its waterholding capacity, color, shelf life, texture, and functional properties of the meat (Fernandez and Tornberg, 1991;Boler et al, 2010). The decline in post-mortem pH from physiological levels to the ultimate pH, reached 8-24 h post-mortem, is a reflection of biochemical changes occurring in the muscle, and is largely dependent on muscle glycogen content at the time of slaughter (Lawrie, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…With the modern Western pig breed origin, the white hybrid boars had higher body weight at 300 days, higher carcass lean percentage and lower backfat thickness, and overall, exhibited better growth rate and carcass performances. At the same time, the black hybrid wild boars, with Chinese indigenous pig breed origin, had higher pH (both pH 1 and pH 2 ) and IMF, lower drip loss and shear force, and more UFC and aromatic amino acids; overall, they had better meat quality and nutritional values (Cameron et al, 1991;Boler et al, 2010;Yang et al, 2010).…”
Section: Traitsmentioning
confidence: 99%